The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3889/oamjms.2017.009
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Father Differences in Postnatal Psychological Distress and Its Determinants in Iran

Abstract: AIM:The aim of this study was to investigate the mother-father differences in Postnatal Psychological Distress (PPD) and its determinants among the parents with 8-weeks old children.MATERIALS AND METHODS:In this cross-sectional study, applying simple random sampling, 306 postnatal parents with an 8-weeks old infant in Saqqez County, Iran, were invited to answer the General Health Questionnaire-28 (GHQ-28) items through the telephone interview. Fifty-eight subjects declined to participate in the study (Response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In the literature, there are studies showing that there is a relationship between the employment status and low-income level of fathers and the risk of depression. 30,31 Similarly, negative situations, such as job loss and low economic situations, have been reported to increase the risk of depression. 12 In addition, in our study, fathers who perceived their financial situation well had higher attachment levels in terms of pleasure in interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are studies showing that there is a relationship between the employment status and low-income level of fathers and the risk of depression. 30,31 Similarly, negative situations, such as job loss and low economic situations, have been reported to increase the risk of depression. 12 In addition, in our study, fathers who perceived their financial situation well had higher attachment levels in terms of pleasure in interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Fathers who perceived their financial situation at a moderate level had higher depression risk levels. In the literature, there are studies showing that there is a relationship between the employment status and low‐income level of fathers and the risk of depression 30,31 . Similarly, negative situations, such as job loss and low economic situations, have been reported to increase the risk of depression 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the mothers with normal vaginal delivery (NVD), the mothers with CS have 5 to 7 times and 4 times higher risks for maternal and neonatal mortality, respectively (Kilsztajn, do Carmo, Machado, Lopes, & Lima, 2007; Nicholson, Yeager, & Macones, 2007; Vafaee, Ghobadi Dashdebi, Momenbellah Fard, Ghalandari, & Gharlipour, 2013). In a recent study, Mahmoodi et al (2017) also found CS as a significant predictor of postnatal psychological distress among new mothers. Choosing CS as the preferred mode of delivery (MOD) among women may be due to different reasons.…”
Section: Introductionmentioning
confidence: 88%
“…According to the manual, based on Goldberg's scoring system, individuals with a score of 4 or below are considered normal in terms of mental health, while individuals with a score of 5 or above are evaluated as “at risk for mental problems.” However, the scale is not an exact measure of final diagnosis. GHQ has been widely used for stroke patients (Hjelle et al., 2019), adult individuals (Noorbala et al., 2017), university students (Ilhan et al., 2014), fathers (Mahmoodi et al., 2017), infertile women (Namdar et al. 2017), and the general population (Ames‐Guerrero et al.…”
Section: Methodsmentioning
confidence: 99%